The prediction of moose-vehicle collisions in Mount Revelstoke and Glacier National Parks, Canada. - Hurley, Michael V. (Author); Rapaport, Eric (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2007)
Moose (Alces alces)-vehicle collisions (MVC) can result in large ecological and socio-economic costs. The increasing number of MVC across Canada are resulting in population-level effects for moose, greater numbers of human injury and mortality, and increased costs to motorists and insurance companies. In my thesis I developed a set of predictive models to better understand MVC and the locations where they might occur on the Trans Canada Highway bisecting Mount Revelstoke and Glacier National Parks in British Columbia, Canada.--P.2. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1327962